Pendampingan Penggunaan Aplikasi Budgeting Pada PT Jaya Selalu Juwana Jawa Tengah Guna Meningkatkan Pendapatan Usaha - Sari, Putri Oktovita (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
The emerging issue in the latest technological advancements has become the most powerful mechanism for advancing living standards and environmental sustainability in the era of the 4.0 revolution, leading to the Society 5.0 era. The combination of technology, which also focuses on humans, will be balanced to advance economic growth. PT Jaya Selalu Juwana, located in Central Java, is a cold storage company engaged in the export of fresh products. This dedication to society is expected to increase knowledge and utilize technological advancements packaged through an application called "budgeting" that can be used to increase the revenue of PT Jaya Selalu Juwana, Central Java. In the future, PT Jaya Selalu Juwana, Central Java, can also analyze business activities ranging from income planning to projecting profit/loss through budgeting software applications that can be downloaded through the web or the Play Store and App Store.